Analisis Pertanggungjawaban Perbankkan terhadap Kerugian Nasabah Akibat Perbuatan Melawan Hukum yang di Lakukan Pegawai Bank - Ibrahim Alfatha Popa; Roy Marthen Moonti; Ibrahim Ahmad (International Forum of Researchers and Lecturers, 2026)
This study aims to analyze the form of bank liability for customer losses caused by unlawful acts committed by bank employees, as well as to identify preventive measures that can be implemented to mitigate internal fraud risks. A normative juridical approach is employed, based on statutory regulations, legal doctrines, and case law analysis. Pursuant to Articles 1365 and 1367 of the Indonesian Civil Code, banks, as employers, are held jointly liable (joint liability) for unlawful acts committed by their employees in the course of their duties. The findings reveal that banks are obliged to compensate customers as part of their civil liability and may subsequently exercise their right of recourse (regres) against the employee responsible. Furthermore, the research highlights the importance of implementing a comprehensive anti-fraud strategy, including internal control systems, employee integrity training, whistleblowing mechanisms, and technology-based monitoring. Strengthening these preventive and accountability measures can reduce the likelihood of employee misconduct and help maintain public trust. This study is expected to serve as both an academic reference and practical guidance for enhancing consumer protection in the Indonesian banking sector.